외사시 환아의 가족 구성원에서 약시 위험인자 존재여부 - 장선영; Sun Young Jang; 최연주; Youn Joo Choi; 김소영; So Young Kim; 장지호; Jee Ho Chang; 박성희; Song Hee Park (Daihan angwa haghoi jabji, 2012)
목적: 외사시 환아의 일차 가족구성원을 대상으로 약시의 위험인자로 알려져 있는 굴절부등, 난시, 원시 및 사시의 비율을 알아보고자 하였다. 대상과 방법: 외사시 환아 58명, 정상대조군 49명의 가족구성원을 대상으로 최대교정시력, 현성굴절이상, 사시검사를 시행하여 의미있는 인자의 유병률을 알아보았으며 대조군의 유병률과 비교하였다. 결과: 환아의 가족구성원 중 65.4% (100/153명)에서 1개 이상의 약시 위험인자가 관찰되었다. 환아의 부모에서 굴절부등, 난시, 원시 및 사시가 각각 18.1% (21명), 31.1% (36명), 2.5% (3명), 11.2% (13명) 관찰되었고 형제자매에서 24.3% (9명), 24.3% (9명), 5.4% (2명), 18.9% (7명) 관찰되었다. 대조군과 비교 시 환아의 부모는 굴절부등(p=0.009), 난시(p=0.034) 및 사시가(p=0.045), 형제자매는 굴절부 등(p=0.021)과 사시(p=0.024)의 빈도가 유의하게 높았다. 결론: 외사시 환아의 일차 가족구성원에서 약시의 위험인자가 높은 비율로 존재하며, 이는 외사시 가족력을 가진 가족구성원의 안과적 선별검사의 근거가 될 수 있다. Purpose: To investigate the prevalence of amblyogenic risk factors in the primary family members (parents, siblings) of patients with exotropia. Methods: The authors of the present study examined primary family members including parents and siblings of 58 exotropia patients in our clinic. Best corrected visual acuity, refractive error, and cover-uncover test were performed. A total of 49 normal children`s family members (control group) were examined in a similar manner. The prevalence of significant ocular findings were determined and compared to the control group, Results: In 58 eligible families (153 subjects except proband), 65.4% had significant ocular findings: In parents, anisometopia, astigmatism, hyperopia, and strabismus were found at a rate of 18.1%, 31.1%, 2.5%, and 11.2%, respectively. In siblings, anisometropia, astigmatism, hyperopia, and strabismus were found at a rate of 24.3%, 24.3%, 5.4%, and 18.9%, respectively. Compared to the control group, in parents of exotropia patients, anisometropia, astigmastim, and strabismus were observed at a higher rate. In siblings, anisometropia, and strabismus were observed at a higher rate. Conclusions: Primary family members of exotropia patients have a high prevalence of amblyogenic risk factors. The present study offers rationale for providing comprehensive eye exams for parents and children with a family history of exotropia.